Preparation method of silicon-based ceramic core with controllable room temperature-high temperature strength
通过在硅基陶瓷型芯的制备过程中引入低温和高温浸渍剂,并采用多工艺处理,解决了硅基陶瓷型芯在室温-高温强度控制方面的不足,实现了型芯的性能稳定性和 Improvement of size accuracy.
Patent Information
- Application Number
- CN202411477841.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
The existing silicon-based ceramic cores have shortcomings in room temperature-high temperature strength control, making it difficult to achieve stable performance improvement, and the internal components of the core are complex and difficult to accurately control.
By mixing the quartz matrix with the mineralization modifier, adding low-temperature impregnating agent and high-temperature impregnating agent, and using processes such as ball milling, hot pressing, debinding and sintering, a silicon-based ceramic core with controllable room temperature-high temperature strength is prepared. .
It achieves simultaneous optimization of room temperature and high temperature strength of the silicon-based ceramic core, improves the performance stability and dimensional accuracy of the core, and reduces the recrystallization rate of single crystal blades.
Smart Images

Figure CN119350008A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of investment casting, and in particular relates to a method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength. Background Art
[0002] Ceramic cores are widely used in the investment casting of hollow turbine blades of aircraft engines. They can provide complex air-cooled inner cavity structures for hollow turbine blades, thereby improving the thrust-to-weight ratio of aircraft engines to meet the growing performance requirements of aircraft engines. At present, the mainstream ceramic cores can be divided into two types: silicon-based and aluminum-based. Among them, silicon-based ceramic cores stand out due to their low thermal expansion coefficient and good solubility, becoming the most widely used ceramic cores.
[0003] In order to improve the qualification rate and dimensional accuracy of single-crystal turbine blades, the requirements for silicon-based ceramic cores have become increasingly stringent. For silicon-based cores, their physical properties are largely controlled by cristobalite from the phase transition of molten quartz. When the cristobalite content is low, the ceramic core exhibits poor physical properties and is easily damaged by impact during wax mold pressing and investment casting. When the cristobalite content is too high, the strength of the core will be too high. During the pouring process, it will interact with the molten metal, resulting in stress concentration and defects such as recrystallization, which is not conducive to the performance of single-crystal blades. On the other hand, cristobalite will undergo phase change again at 180-270°C, causing volume shrinkage, and the microcracks caused by shrinkage stress will also cause the performance of the core to deteriorate. Therefore, silicon-based ceramic cores with appropriate room temperature-high temperature strength are the focus of current research.
[0004] At present, the research on the strength of silicon-based ceramic cores is mainly focused on the optimization of sintering system and the selection of mineralizers. The performance is improved by adding a second reinforcement phase, but the introduction of multiple mineralizers will complicate the internal composition of the core and make it difficult to accurately control its strength. The improvement of core strength by sintering system optimization is relatively limited, and it is difficult to achieve simultaneous optimization of room temperature and high temperature strength. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength in view of the deficiencies of the above-mentioned prior art, which can improve the performance stability of the silicon-based ceramic core.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength, the method comprising:
[0007] S1, mixing a quartz matrix and a mineralizing modifier to obtain a silicon-based composite material;
[0008] S2, mixing the silicon-based composite material obtained in S1 with a low-temperature impregnating agent, ball milling at a rotation speed of 300 rpm for 6 h to 10 h, drying at a temperature of 70° C. to 100° C. for 6 h to 10 h, and sieving through 100 mesh to obtain a modified silicon-based powder;
[0009] S3, mixing the modified silicon-based powder obtained in S1 with a plasticizer to obtain a ceramic slurry;
[0010] S4, hot pressing the ceramic slurry obtained in S3 at a pressure of 5MPa to 10MPa and a temperature of 80°C to 100°C for 20s to 60s to obtain a ceramic core blank;
[0011] S5, debinding and sintering the ceramic core blank obtained in S4 in sequence to obtain a silicon-based ceramic core;
[0012] The debinding method comprises: heating the temperature at a heating rate of 0.1°C / min to 0.5°C / min, first heating the temperature to 100°C, keeping the temperature for 1h to 2h; then heating the temperature to 200°C, keeping the temperature for 1h to 2h; then heating the temperature to 300°C, keeping the temperature for 1h to 2h; then heating the temperature to 400°C, keeping the temperature for 1h to 2h;
[0013] The sintering method comprises: heating to 1150°C to 1250°C at a heating rate of 1.5°C / min to 3.5°C / min, maintaining the temperature for 6h to 10h, and then naturally cooling to room temperature;
[0014] S6. Soak the silicon-based ceramic core obtained in S5 in a high-temperature impregnating agent for 4 hours to 8 hours, and then dry it at room temperature for 6 hours to 10 hours to obtain a silicon-based ceramic core with controllable room temperature-high temperature strength.
[0015] Preferably, the quartz substrate in S1 is fused quartz.
[0016] Preferably, the mineralizing modifier in S1 is a mixture of mullite, mullite fiber and silicon carbide.
[0017] Preferably, the mass fraction of the quartz matrix in the silicon-based composite material in S1 is 80%.
[0018] Preferably, the mass ratio of the silicon-based composite material to the low-temperature impregnating agent in S2 is 2:1.
[0019] Preferably, the low-temperature impregnating agent in S2 is silica sol.
[0020] Preferably, the plasticizer in S3 is composed of the following raw materials in mass fractions: 5% beeswax, 5% polyethylene, and the remainder paraffin.
[0021] Preferably, the mass fraction of the modified silicon-based powder in the ceramic slurry in S3 is 85%.
[0022] Preferably, the high-temperature impregnating agent in S6 is yttrium sol, titanium sol or phosphoric acid solution.
[0023] Preferably, the silicon-based ceramic core with controllable room temperature-high temperature strength in S6 has a bending strength of 15.83 MPa to 19.23 MPa at 25°C and a bending strength of 22.47 MPa to 28.54 MPa at 1540°C.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The present invention introduces sol-like substances into the preparation of silicon-based ceramic cores in the form of low-temperature and high-temperature impregnants, respectively. In the low-temperature impregnant, water vapor in the impregnant can contact molten quartz during the sintering process, forming OH-bonds on the interface, so that the [Si-O-Si] bonds with stronger bond strength are replaced by the weaker [Si-OH-HO-Si] bonds, so as to promote the phase transition of molten quartz to cristobalite, thereby affecting the bending strength of the core, and the cristobalite content can be finely designed by the impregnation time or sol concentration, so as to adjust the comprehensive performance of the silicon-based core.
[0026] On the other hand, the high temperature impregnant mainly plays the role of inhibiting the precipitation of quartz and preventing the high temperature strength of the silicon-based core from being too high. 3+ 、Ti 4+ , P 5+ Plasma can effectively shield oxygen atoms and hinder their movement, thereby inhibiting crystallization. Moreover, when the diffusion of oxygen atoms is inhibited, the degree of densification inside the core decreases, the creep rate decreases, the porosity is further increased, the high-temperature creep resistance is improved, and it is also beneficial to the corrosion resistance and dimensional accuracy of the core. Therefore, the present invention simultaneously achieves the improvement of the comprehensive performance of the silicon-based ceramic core.
[0027] The present invention can accurately control the strength of the silicon-based core, avoid the complication of the internal components of the core, reduce the recrystallization rate of the single crystal blade, is of great help to the investment casting process, and can be better applied to the casting of single crystal blades.
[0028] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a room temperature microscopic morphology image of the silicon-based ceramic core prepared in Example 1 of the present invention.
[0030] Figure 2 This is a high-temperature microscopic morphology image of the silicon-based ceramic core prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The silica sol, yttrium sol and titanium sol in the following examples are commercially available from AVIC Armor Technology Co., Ltd.
[0032] Example 1
[0033] The method for preparing the silicon-based ceramic core with controllable room temperature-high temperature strength of this embodiment is as follows:
[0034] S1. Mixing a quartz matrix (fused quartz) and a mineralizing modifier to obtain a silicon-based composite material; the mineralizing modifier is a mixture of mullite, mullite fiber and silicon carbide in a mass ratio of 2:1:1; the fused quartz is a powder with an average particle size of 5 μm; the mineralizing modifier is a powder with an average particle size of 20 μm;
[0035] The mass fraction of the quartz matrix in the silicon-based composite material is 80%;
[0036] S2, mixing the silicon-based composite material obtained in S1 with a low-temperature impregnating agent (silica sol), ball milling at a rotation speed of 300 rpm for 8 hours, drying at a temperature of 800° C. for 6 hours, and sieving through 100 meshes to obtain a modified silicon-based powder; the mass ratio of the silicon-based composite material to the low-temperature impregnating agent is 2:1;
[0037] S3, mixing the modified silicon-based powder obtained in S1 with a plasticizer to obtain a ceramic slurry; the plasticizer is composed of the following raw materials in mass fractions: 5% beeswax, 5% polyethylene, and the remainder paraffin;
[0038] The mass fraction of the modified silicon-based powder in the ceramic slurry is 85%;
[0039] S4, hot pressing the ceramic slurry obtained in S3 at a pressure of 7 MPa and a temperature of 90° C. for 30 seconds to obtain a ceramic core blank;
[0040] S5, debinding and sintering the ceramic core blank obtained in S4 in sequence to obtain a silicon-based ceramic core;
[0041] The debinding method is as follows: heating treatment is performed at a heating rate of 0.1°C / min, first heating to 100°C, keeping the temperature for 2 hours; then heating to 200°C, keeping the temperature for 2 hours; then heating to 300°C, keeping the temperature for 2 hours; then heating to 400°C, keeping the temperature for 2 hours;
[0042] The sintering method is: heating to 1200°C at a heating rate of 2°C / min, keeping the temperature constant for 6 hours, and then naturally cooling to room temperature;
[0043] S6. Soak the silicon-based ceramic core obtained in S5 in a high-temperature impregnating agent (yttrium sol) for 6 hours, and then dry it at room temperature for 8 hours to obtain a silicon-based ceramic core with controllable room temperature-high temperature strength.
[0044] Comparative Example 1
[0045] The preparation method of the silicon-based ceramic core of this comparative example is:
[0046] The preparation method of the silicon-based ceramic core in this comparative example is the same as that in Example 1, except that no low-temperature impregnating agent is added, that is, the operation of step S2 in Example 1 is not performed.
[0047] Comparative Example 2
[0048] The preparation method of the silicon-based ceramic core of this comparative example is:
[0049] The preparation method of the silicon-based ceramic core in this comparative example is the same as that in Example 1, except that no high-temperature impregnating agent is added, that is, the operation of step S6 in Example 1 is not performed.
[0050] Example 2
[0051] The method for preparing the silicon-based ceramic core with controllable room temperature-high temperature strength of this embodiment is as follows:
[0052] S1. Mixing a quartz matrix (fused quartz) and a mineralizing modifier to obtain a silicon-based composite material; the mineralizing modifier is a mixture of mullite, mullite fiber and silicon carbide in a mass ratio of 2:1:1; the fused quartz is a powder with an average particle size of 5 μm; the mineralizing modifier is a powder with an average particle size of 20 μm;
[0053] The mass fraction of the quartz matrix in the silicon-based composite material is 80%;
[0054] S2, mixing the silicon-based composite material obtained in S1 with a low-temperature impregnating agent (silica sol), ball milling at a rotation speed of 300 rpm for 6 hours, drying at a temperature of 70° C. for 10 hours, and sieving through 100 meshes to obtain a modified silicon-based powder; the mass ratio of the silicon-based composite material to the low-temperature impregnating agent is 2:1;
[0055] S3, mixing the modified silicon-based powder obtained in S1 with a plasticizer to obtain a ceramic slurry; the plasticizer is composed of the following raw materials in mass fractions: 5% beeswax, 5% polyethylene, and the remainder paraffin;
[0056] The mass fraction of the modified silicon-based powder in the ceramic slurry is 85%;
[0057] S4, hot pressing the ceramic slurry obtained in S3 at a pressure of 5 MPa and a temperature of 80° C. for 60 seconds to obtain a ceramic core blank;
[0058] S5, debinding and sintering the ceramic core blank obtained in S4 in sequence to obtain a silicon-based ceramic core;
[0059] The debinding method is as follows: heating treatment is performed at a heating rate of 0.5°C / min, first heating to 100°C, keeping the temperature for 1 hour; then heating to 200°C, keeping the temperature for 1 hour; then heating to 300°C, keeping the temperature for 1 hour; then heating to 400°C, keeping the temperature for 1 hour;
[0060] The sintering method is: heating to 1250°C at a heating rate of 1.5°C / min, keeping the temperature constant for 10 hours, and then naturally cooling to room temperature;
[0061] S6. Soak the silicon-based ceramic core obtained in S5 in a high-temperature impregnating agent (titanium sol) for 4 hours, and then dry it at room temperature for 10 hours to obtain a silicon-based ceramic core with controllable room temperature-high temperature strength.
[0062] Example 3
[0063] The method for preparing the silicon-based ceramic core with controllable room temperature-high temperature strength of this embodiment is as follows:
[0064] S1. Mixing a quartz matrix (fused quartz) and a mineralizing modifier to obtain a silicon-based composite material; the mineralizing modifier is a mixture of mullite, mullite fiber and silicon carbide in a mass ratio of 2:1:1; the fused quartz is a powder with an average particle size of 5 μm; the mineralizing modifier is a powder with an average particle size of 20 μm;
[0065] The mass fraction of the quartz matrix in the silicon-based composite material is 80%;
[0066] S2, mixing the silicon-based composite material obtained in S1 with a low-temperature impregnating agent (silica sol), ball milling at a rotation speed of 300 rpm for 10 hours, drying at a temperature of 100° C. for 8 hours, and sieving through 100 meshes to obtain a modified silicon-based powder; the mass ratio of the silicon-based composite material to the low-temperature impregnating agent is 2:1;
[0067] S3, mixing the modified silicon-based powder obtained in S1 with a plasticizer to obtain a ceramic slurry; the plasticizer is composed of the following raw materials in mass fractions: 5% beeswax, 5% polyethylene, and the remainder paraffin;
[0068] The mass fraction of the modified silicon-based powder in the ceramic slurry is 85%;
[0069] S4, hot pressing the ceramic slurry obtained in S3 at a pressure of 10 MPa and a temperature of 100° C. for 20 seconds to obtain a ceramic core blank;
[0070] S5, debinding and sintering the ceramic core blank obtained in S4 in sequence to obtain a silicon-based ceramic core;
[0071] The debinding method is as follows: heating treatment is performed at a heating rate of 0.2°C / min, first heating to 100°C, keeping the temperature for 1.5 hours; then heating to 200°C, keeping the temperature for 1.5 hours; then heating to 300°C, keeping the temperature for 1.5 hours; then heating to 400°C, keeping the temperature for 1.5 hours;
[0072] The sintering method is: heating to 1150°C at a heating rate of 3.5°C / min, keeping the temperature constant for 8 hours, and then naturally cooling to room temperature;
[0073] S6. Soak the silicon-based ceramic core obtained in S5 in a high-temperature impregnating agent (a phosphoric acid solution with a mass fraction of 50%) for 8 hours, and then dry it at room temperature for 6 hours to obtain a silicon-based ceramic core with controllable room temperature-high temperature strength.
[0074] Example 4
[0075] The method for preparing the silicon-based ceramic core with controllable room temperature-high temperature strength of this embodiment is as follows:
[0076] S1. Mixing a quartz matrix (fused quartz) and a mineralizing modifier to obtain a silicon-based composite material; the mineralizing modifier is a mixture of mullite, mullite fiber and silicon carbide in a mass ratio of 2:1:1; the fused quartz is a powder with an average particle size of 5 μm; the mineralizing modifier is a powder with an average particle size of 20 μm;
[0077] The mass fraction of the quartz matrix in the silicon-based composite material is 80%;
[0078] S2, mixing the silicon-based composite material obtained in S1 with a low-temperature impregnating agent (silica sol), ball milling at a rotation speed of 300 rpm for 7 hours, drying at a temperature of 90° C. for 7 hours, and sieving through 100 meshes to obtain a modified silicon-based powder; the mass ratio of the silicon-based composite material to the low-temperature impregnating agent is 2:1;
[0079] S3, mixing the modified silicon-based powder obtained in S1 with a plasticizer to obtain a ceramic slurry; the plasticizer is composed of the following raw materials in mass fractions: 5% beeswax, 5% polyethylene, and the remainder paraffin;
[0080] The mass fraction of the modified silicon-based powder in the ceramic slurry is 85%;
[0081] S4, hot pressing the ceramic slurry obtained in S3 at a pressure of 8 MPa and a temperature of 90° C. for 40 seconds to obtain a ceramic core blank;
[0082] S5, debinding and sintering the ceramic core blank obtained in S4 in sequence to obtain a silicon-based ceramic core;
[0083] The debinding method is as follows: heating treatment is performed at a heating rate of 0.4°C / min, first heating to 100°C, keeping the temperature for 1 hour; then heating to 200°C, keeping the temperature for 1 hour; then heating to 300°C, keeping the temperature for 1 hour; then heating to 400°C, keeping the temperature for 1 hour;
[0084] The sintering method is: heating to 1200°C at a heating rate of 2°C / min, keeping the temperature constant for 8 hours, and then naturally cooling to room temperature;
[0085] S6. Soak the silicon-based ceramic core obtained in S5 in a high-temperature impregnating agent (yttrium sol) for 8 hours, and then dry it at room temperature for 8 hours to obtain a silicon-based ceramic core with controllable room temperature-high temperature strength.
[0086] Example 5
[0087] The method for preparing the silicon-based ceramic core with controllable room temperature-high temperature strength of this embodiment is as follows:
[0088] S1. Mixing a quartz matrix (fused quartz) and a mineralizing modifier to obtain a silicon-based composite material; the mineralizing modifier is a mixture of mullite, mullite fiber and silicon carbide in a mass ratio of 2:1:1; the fused quartz is a powder with an average particle size of 5 μm; the mineralizing modifier is a powder with an average particle size of 20 μm;
[0089] The mass fraction of the quartz matrix in the silicon-based composite material is 80%;
[0090] S2, mixing the silicon-based composite material obtained in S1 with a low-temperature impregnating agent (silica sol), ball milling at a rotation speed of 300 rpm for 10 hours, drying at a temperature of 80° C. for 6 hours, and sieving through 100 meshes to obtain a modified silicon-based powder; the mass ratio of the silicon-based composite material to the low-temperature impregnating agent is 2:1;
[0091] S3, mixing the modified silicon-based powder obtained in S1 with a plasticizer to obtain a ceramic slurry; the plasticizer is composed of the following raw materials in mass fractions: 5% beeswax, 5% polyethylene, and the remainder paraffin;
[0092] The mass fraction of the modified silicon-based powder in the ceramic slurry is 85%;
[0093] S4, hot pressing the ceramic slurry obtained in S3 at a pressure of 6 MPa and a temperature of 85° C. for 50 seconds to obtain a ceramic core blank;
[0094] S5, debinding and sintering the ceramic core blank obtained in S4 in sequence to obtain a silicon-based ceramic core;
[0095] The debinding method is as follows: heating treatment is performed at a heating rate of 0.5°C / min, first heating to 100°C, keeping the temperature for 2 hours; then heating to 200°C, keeping the temperature for 2 hours; then heating to 300°C, keeping the temperature for 2 hours; then heating to 400°C, keeping the temperature for 2 hours;
[0096] The sintering method is: heating to 1200°C at a heating rate of 3°C / min, keeping the temperature constant for 8 hours, and then cooling naturally to room temperature;
[0097] S6. Soak the silicon-based ceramic core obtained in S5 in a high-temperature impregnating agent (a phosphoric acid solution with a mass fraction of 50%) for 4 hours, and then dry it at room temperature for 8 hours to obtain a silicon-based ceramic core with controllable room temperature-high temperature strength.
[0098] The above performance tests are issued in accordance with HB 5353.3-2004, and the test temperatures are room temperature 25°C and high temperature 1540°C. Comparative Example 1 does not use a low-temperature impregnant, and the lower bending strength easily causes the ceramic core to be damaged during the casting process, resulting in blade casting failure. Comparative Example 2 does not use a high-temperature impregnant, and the higher high-temperature bending strength causes the ceramic core to interact with the metal liquid during the casting process, causing stress concentration and recrystallization, resulting in the appearance of impurities in the single crystal blade, affecting the final performance of the blade.
[0099] Table 1 Performance test of ceramic cores prepared in Examples 1-5 and Comparative Examples 1-2
[0100]
[0101]
[0102] As can be seen from Table 1, Examples 1-5 all control the room temperature-high temperature strength of the silicon-based ceramic core within a reasonable range, which can effectively improve the success rate of the silicon-based ceramic core in the blade casting process. Comparative Examples 1-2 are respectively limited by lower room temperature strength and too high high temperature strength, which have an adverse effect on blade casting.
[0103] Depend on Figure 1 It can be seen that by adding a low-temperature impregnating agent (silica sol), amorphous SiO2 nanoparticles are precipitated during the sintering process. The extremely high specific surface energy significantly promotes sintering densification and improves the room temperature flexural strength of the ceramic core.
[0104] Depend on Figure 2 It can be seen that after the secondary sintering at 1540℃, obvious liquid phase sintering occurs in the sample, and a large amount of fused quartz crystallizes to form cristobalite. The high-temperature impregnating agent decomposes high-charge, small-volume ions at high temperatures, such as Y 3+ 、Ti 4+ , P 5+Plasma inhibits the precipitation of cristobalite. The internal pores also prove the inhibitory effect of high-temperature impregnants on sintering, which can prevent the core from having too high a high-temperature strength, thereby improving the success rate of blade casting.
[0105] Embodiments 1-5 of the present invention can well regulate the room temperature-high temperature strength of the silicon-based ceramic core. By improving the room temperature strength through the low temperature impregnating agent, the ceramic core can be prevented from being damaged by the impact of the molten metal during the pouring process. The addition of the high temperature impregnating agent can reduce the stress concentration caused by the interaction between the ceramic core and the molten metal, and avoid recrystallization. Therefore, this technology can be well applied to the investment casting process of the ceramic core.
[0106] The present invention introduces sol-like substances into the preparation of silicon-based ceramic cores in the form of low-temperature and high-temperature impregnants, respectively. In the low-temperature impregnant, water vapor in the impregnant can contact molten quartz during the sintering process, forming OH-bonds on the interface, so that the [Si-O-Si] bonds with stronger bond strength are replaced by the weaker [Si-OH-HO-Si] bonds, so as to promote the phase transition of molten quartz to cristobalite, thereby affecting the bending strength of the core, and the cristobalite content can be finely designed by the impregnation time or sol concentration, so as to adjust the comprehensive performance of the silicon-based core.
[0107] On the other hand, the high temperature impregnant mainly plays the role of inhibiting the precipitation of quartz and preventing the high temperature strength of the silicon-based core from being too high. 3+ 、Ti 4+ , P 5+ Plasma can effectively shield oxygen atoms and hinder their movement, thereby inhibiting crystallization. Moreover, when the diffusion of oxygen atoms is inhibited, the degree of densification inside the core decreases, the creep rate decreases, the porosity is further increased, the high-temperature creep resistance is improved, and it is also beneficial to the corrosion resistance and dimensional accuracy of the core. Therefore, the present invention simultaneously achieves the improvement of the comprehensive performance of the silicon-based ceramic core.
[0108] The present invention can accurately control the strength of the silicon-based core, avoid the complication of the internal components of the core, reduce the recrystallization rate of the single crystal blade, is of great help to the investment casting process, and can be better applied to the casting of single crystal blades.
[0109] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength, characterized in that: The method is: S1, mixing a quartz matrix and a mineralizing modifier to obtain a silicon-based composite material; S2, mixing the silicon-based composite material obtained in S1 with a low-temperature impregnating agent, ball milling at a rotation speed of 300 rpm for 6 h to 10 h, drying at a temperature of 70° C. to 100° C. for 6 h to 10 h, and sieving through 100 mesh to obtain a modified silicon-based powder; S3, mixing the modified silicon-based powder obtained in S1 with a plasticizer to obtain a ceramic slurry; S4, hot pressing the ceramic slurry obtained in S3 at a pressure of 5MPa to 10MPa and a temperature of 80°C to 100°C for 20s to 60s to obtain a ceramic core blank; S5, debinding and sintering the ceramic core blank obtained in S4 in sequence to obtain a silicon-based ceramic core; The debinding method comprises: heating the temperature at a heating rate of 0.1°C / min to 0.5°C / min, first heating the temperature to 100°C, keeping the temperature for 1h to 2h; then heating the temperature to 200°C, keeping the temperature for 1h to 2h; then heating the temperature to 300°C, keeping the temperature for 1h to 2h; then heating the temperature to 400°C, keeping the temperature for 1h to 2h; The sintering method comprises: heating to 1150°C to 1250°C at a heating rate of 1.5°C / min to 3.5°C / min, maintaining the temperature for 6h to 10h, and then naturally cooling to room temperature; S6. Soak the silicon-based ceramic core obtained in S5 in a high-temperature impregnating agent for 4 hours to 8 hours, and then dry it at room temperature for 6 hours to 10 hours to obtain a silicon-based ceramic core with controllable room temperature-high temperature strength.
2. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The quartz substrate in S1 is fused quartz.
3. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The mineralizing modifier described in S1 is a mixture of mullite, mullite fiber and silicon carbide.
4. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The mass fraction of the quartz matrix in the silicon-based composite material in S1 is 80%.
5. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The mass ratio of the silicon-based composite material to the low-temperature impregnating agent in S2 is 2:
1.
6. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The low-temperature impregnating agent in S2 is silica sol.
7. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The plasticizer in S3 is composed of the following raw materials in mass fractions: 5% beeswax, 5% polyethylene, and the remainder paraffin.
8. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The mass fraction of the modified silicon-based powder in the ceramic slurry in S3 is 85%.
9. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The high-temperature impregnating agent in S6 is yttrium sol, titanium sol or phosphoric acid solution.
10. The method for preparing a silicon-based ceramic core with controllable room temperature-high temperature strength according to claim 1, characterized in that: The silicon-based ceramic core with controllable room temperature-high temperature strength described in S6 has a bending strength of 15.83MPa to 19.23MPa at 25°C and a bending strength of 22.47MPa to 28.54MPa at 1540°C.
Citation Information
Patent Citations
Silicon-based ceramic core preparation method
CN105732014A
Silicon-based ceramic core material, preparation method and silicon-based ceramic core
CN114907133A
Silicon oxide-based ceramic core and preparation method thereof
CN115196981A
Method for producing silica-base ceramic core capable of adjusting a thermal expansion coefficient
KR1020150124899A
Cited By
Preparation method and application of 3D printing silicon-based ceramic core
CN117534451A
A preparation method and application of a 3D printed silicon-based ceramic core
CN117534451B